Progress in Ameliorating Beneficial Characteristics of Microbial Cellulases by Genetic Engineering Approaches for Cellulose Saccharification - Dadwal, Anica; Sharma, Shilpa; Satyanarayana, Tulasi (Frontiers in Microbiology, 2020)
Lignocellulosic biomass is a renewable and sustainable energy source. Cellulases are the enzymes that cleave β-1, 4-glycosidic linkages in cellulose to liberate sugars that are fermented to ethanol. Low enzyme activity and yield, and thermostability are, however, some of the limitations posing hurdles in saccharification of lignocellulosic residues. Recent advancements in synthetic and systems biology have generated immense interest in metabolic and genetic engineering that has led to the development of sustainable technology for saccharification of lignocellulosics in the last couple of decades. There have been several attempts in applying genetic engineering in the production of a repertoire of cellulases at low cost with high biomass saccharification efficiency. A diverse range of cellulases are produced by different microbes, some of which are being engineered to evolve robust cellulases. This review summarizes various successful genetic engineering strategies employed for improving cellulase kinetics and ameliorate cellulolytic efficiency.